xsqared+3xsquared=10squared

Simple and best practice solution for xsqared+3xsquared=10squared equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for xsqared+3xsquared=10squared equation:


Simplifying
xsqared + 3xsquared = 10squared

Reorder the terms:
3adeqrsux + adeqrsx = 10squared

Solving
3adeqrsux + adeqrsx = 10adeqrsu

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-10adeqrsu' to each side of the equation.
3adeqrsux + -10adeqrsu + adeqrsx = 10adeqrsu + -10adeqrsu

Reorder the terms:
-10adeqrsu + 3adeqrsux + adeqrsx = 10adeqrsu + -10adeqrsu

Combine like terms: 10adeqrsu + -10adeqrsu = 0
-10adeqrsu + 3adeqrsux + adeqrsx = 0

Factor out the Greatest Common Factor (GCF), 'adeqrs'.
adeqrs(-10u + 3ux + x) = 0

Subproblem 1

Set the factor 'adeqrs' equal to zero and attempt to solve: Simplifying adeqrs = 0 Solving adeqrs = 0 Move all terms containing a to the left, all other terms to the right. Simplifying adeqrs = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-10u + 3ux + x)' equal to zero and attempt to solve: Simplifying -10u + 3ux + x = 0 Solving -10u + 3ux + x = 0 Move all terms containing a to the left, all other terms to the right. Add '10u' to each side of the equation. -10u + 3ux + 10u + x = 0 + 10u Reorder the terms: -10u + 10u + 3ux + x = 0 + 10u Combine like terms: -10u + 10u = 0 0 + 3ux + x = 0 + 10u 3ux + x = 0 + 10u Remove the zero: 3ux + x = 10u Add '-3ux' to each side of the equation. 3ux + -3ux + x = 10u + -3ux Combine like terms: 3ux + -3ux = 0 0 + x = 10u + -3ux x = 10u + -3ux Add '-1x' to each side of the equation. x + -1x = 10u + -3ux + -1x Combine like terms: x + -1x = 0 0 = 10u + -3ux + -1x Simplifying 0 = 10u + -3ux + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 24x+4(6-x)=2(x+19)+4x | | 2(w-8)+3w= | | 16x^2+3x-4=0 | | 6-2(4-4x)=0 | | 35x^2+49x=168 | | 5(w-4)-(1-8w)=12w | | 35x^2+49=168x | | 48-2x=5x+7 | | -(-2+n)=-4+11n | | 35x^2+49=168 | | 4y^2-4y-24=0 | | 3-2(8x+4)=5 | | 6-(2x-6)=7-3x | | -4x+(4+6x)=10 | | 5x+2=25+50x | | 4t^2-13t-35=0 | | 3x^3-2x^2-3x-4= | | x^2+7x+3=3 | | 374+78x+4x^2=644 | | 287.64=9(0.05m+21.70+0.30(21.70)) | | -6-(4-b)=30 | | 3y+9x+5y= | | 9y-8=8y | | 0=-16t^2+75t-23 | | .4+7=7 | | -x+7=5x+11 | | 12t+4=16t-8 | | -7x+3-5x=3x-31+2x | | 7x+21=-21-3x | | 6-1.5x=24 | | 3ln(x)+2x=3ln(20)+ln(10) | | x(-13-x)=42 |

Equations solver categories